Sistem Pendukung Keputusan Seleksi Penerimaan Karyawan Baru dengan Menerapkan Kombinasi Metode ANP-TOPSIS - Butar Butar, Roi Martin; Murdani, Murdani; Utomo, Dito Putro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Acceptance of new employees at PT Exprvet Nasuba Medan is one of the routine activities carried out every year, in order to find reliable candidates. The problem that occurs is that the selection is still random, not objective and impure, because it is caused by a third party in the recruitment of new employees. So that the decisions taken can trigger a tendency towards subjectivity in one of the prospective registrants which results in brokering at the selection stage. To overcome this problem, a Decision Support System (DSS) was developed that used a combination of the ANP-TOPSIS method in selecting and accepting new employees by finding the best solution based on that method. In this study, the ANP was used to assign a weight to each criterion. The weight is calculated by the TOPSIS method of ranking. Based on the results of the ranking calculations obtained using a combination of the ANP-TOPSIS method. The highest score obtained based on alternative criteria and data, showing the highest preference value is Sukur Jaya Sinaga with an average score of 0.9182 as a rank 1, Hemansyah with an average value of 0.6666 as a rank 2. And Rudi Kesuma with an average score The average is 0.6648 ranking 3. So that it can be concluded from the results of the calculations of the two combinations of the ANP-TOPSIS method, that Sukur Jaya Sinaga is ranked first and the highest value is based on the results of the weighting of the ANP method and then calculated by the Topsis method for ranking.